SARS-CoV-2 and influenza vaccine hesitancy during the COVID-19 pandemic in a dynamic perspective - Valentina Gerussi; Maddalena Peghin; Alvisa Palese; Maria De Martino; Elena Graziano; Stefania Chiappinotto; Federico Fonda; Giulia Bontempo; Tosca Semenzin; Luca Martini; Miriam Isola; Carlo Tascini (Taylor & Francis Group, 2024)
To investigate the dynamic evolution of vaccine hesitancy toward both COVID-19 and influenza in a context characterized by the compresence of SARS-CoV-2 pandemic and seasonal flu epidemics, a two times repeated cross-sectional exploratory design was performed at Udine Hospital (Italy) following a cohort of 479 adult patients with a previous history of SARS-CoV-2 infection in 2020. Vaccine attitude was assessed through standardized telephone interviews performed at 12 and 18 months after the acute illness. The first interview reported the success of the 2020/21 seasonal influenza immunization with 46.8% (224/479) of the participants showing a positive attitude, especially the elderly and people with comorbidities (p < .001), but the investigation conducted at 18 months showed a drastic drop in flu shot acceptance (30/166, 18.1%). On the other hand, a great increase in vaccinations against SARS-CoV-2 occurred after the introduction of Green Pass (26.7% vs 72.9%). The major drivers of flu vaccine skepticism were represented by the feeling of protection regardless of prevention and by concerns regarding vaccines safety and efficacy; conversely compulsory strategies seemed to play a secondary role, since only a minority of the participants identified in the restrictions induced by the certification the major incentive to get immunized against SARS-CoV-2. The focus on this peculiar historical period helps to take a step forward in the comprehension of the complexity and dynamicity of the vaccine hesitancy phenomenon. Future vaccination campaigns will need to consider the role of personal opinions and emotions, interpreted according to the social and political context.